RETRACTED: Spinel zinc ferrite nanoparticles: an active nanocatalyst for microwave irradiated solvent free synthesis of chalcones - Ravikumar M Borade; Sandeep B Somvanshi; Swati B Kale; Rajendra P Pawar; K M Jadhav (Materials Research Express)
A profoundly effective magnetically recoverable nano zinc ferrite nanocatalyst was fabricated by means of sol-gel auto ignition strategy. The synthesized nanocatalyst has been completely portrayed by standard techniques for structural, morphological, compositional, surface, magnetic, dielectric, optical and photoluminescence properties individually. The x-ray diffraction pattern affirmed the arrangement of cubic spinel structure with an average crystallite size of 21 nm. FE-SEM images uncovered the circular morphology with nanometric average grain measure (37 nm). The surface area, pore volume and pore radius was observed to be 39.812 m ^2 g ^−1 , 3.41 cc g ^−1 and 1.34 nm individually from BET analysis. VSM investigation demonstrated the superparamgnetic nature of the prepared sample with moderate magnetization value and negligible coercivity. The optical band gap deduced from UV–vis spectra was observed to be 2.098 eV. Every one of these properties of zinc nanoferrite makes them brilliant contender for microwave radiation absorption. Further, a proficient and versatile microwave irradiated solvent free synthesis of chalcone derivatives has been developed using prepared zinc nanoferrite catalyst. The remarkable highlights of this new protocol are solvent free reaction, economical cheapness, eco-friendliness, high yields, reduced reaction times and easy recovery and reuse of zinc ferrite nanocatalyst.